2016
DOI: 10.15376/biores.11.4.8285-8296
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Impregnated and Heat Treated Oriental Beech Wood

Abstract: The main purpose of this study was to investigate mechanical properties such as the modulus of rupture (MOR) and compression strength parallel to grain (CSPG) of impregnated and heat-treated Oriental beech (Fagus orientalis L.) wood. Some copper and boron containing impregnation chemicals such as Wolmanit CX-8 (WCX-8) and Celcure AC-500 (CAC-500) were used. Wood specimens were impregnated 2% aqueous solution of the chemicals according to ASTM D1413-07e1 standard. The wood specimens were heated at 150 and 175 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
3
6
0
2
Order By: Relevance
“…Some researchers have reported an increase in gloss values on wood surfaces exposed to artificial weathering under controlled exposure conditions [ 109 ]. Other studies have reported a reduction in glossiness of wood surfaces [ [110] , [111] , [112] ]. The removal of early wood tracheids results in elevated microroughness, while the exposed middle lamellae surfaces reflect light more specularly than the cut/broken cell wall.…”
Section: Discussionmentioning
confidence: 96%
“…Some researchers have reported an increase in gloss values on wood surfaces exposed to artificial weathering under controlled exposure conditions [ 109 ]. Other studies have reported a reduction in glossiness of wood surfaces [ [110] , [111] , [112] ]. The removal of early wood tracheids results in elevated microroughness, while the exposed middle lamellae surfaces reflect light more specularly than the cut/broken cell wall.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are also some studies [ 15 ] that first heat-treated wood and then impregnated it, and they all used medium-temperature heat-treated wood to improve the physical and mechanical properties. In addition, some studies are also devoted to the functional modification of wood, and the combination of dipping and heat treatment is used to enhance the antibacterial properties of wood [ 16 ], anticorrosion [ 17 ], and flame retardancy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ce test a l'avantage d'être accéléré par rapport au vieillissement naturel [10][11], qui dure un an et qui présente souvent des problèmes de répétabilité et de reproductibilité.…”
Section: Introductionunclassified